2008
DOI: 10.1111/j.1600-9657.2007.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and environment of dental injuries in 12‐ to 14‐year‐old Ontario schoolchildren

Abstract: This study reports on the etiology and environment where dental injuries occurred and assesses the relationship between dental trauma, socio-economic status and dental caries experience. A population-based, matched case-comparison study was undertaken in 30 schools in two Ontario communities. Dental hygienists calibrated in the use of the Dental Trauma Index (DTI) screened 2422 children aged 12 and 14 years using DTI and Decayed, Missing and Filled Teeth indices. Cases (n = 135) were children with evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
3
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(105 citation statements)
references
References 15 publications
10
73
3
19
Order By: Relevance
“…However, most studies of TDI have reported its prevalence in permanent teeth. [1][2][3][4] Although several recent studies have assessed the prevalence of TDI in primary teeth and its associations with socioeconomic indicators, the results have been inconsistent and conflicting. [5][6][7][8][9][10] In Brazil, the TDI prevalence in primary teeth ranges from 9.4% to 41.6%, [5][6] and there is evidence that TDI prevalence in deciduous teeth is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies of TDI have reported its prevalence in permanent teeth. [1][2][3][4] Although several recent studies have assessed the prevalence of TDI in primary teeth and its associations with socioeconomic indicators, the results have been inconsistent and conflicting. [5][6][7][8][9][10] In Brazil, the TDI prevalence in primary teeth ranges from 9.4% to 41.6%, [5][6] and there is evidence that TDI prevalence in deciduous teeth is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Outros fatores etiológicos relatados O resultado da maioria dos estudos apontou o gênero masculino como o mais acometido por traumatismo dentário 3,7,9-11,13-15,23-24 e a principal etiologia a queda [13][14][15][16][17] . Associação estatisticamente significante entre gênero masculino e queda foi reportada na Nigéria 13 , no Irã 15 e no Canadá 21 . Estudos mostraram que os meninos estão mais ligados a atividades esportivas ou brincadeiras em locais abertos, sendo por este motivo mais exposto a acidentes intencionais ou não, podendo provocar traumatismo dentário 20,23 .…”
Section: Resultsunclassified
“…As causas do traumatismo dentário são amplamente conhecidas, sendo as principais quedas, colisões contra objetos ou pessoas, acidentes automobilísticos, práticas esportivas e violência 3,5,8,[11][12][13][14][15][16][17][18][19][20][21] . A maioria dos estudos de frequência que avaliaram as causas do traumatismo dentário apontou a queda como o principal fator etiológico [13][14][15][16][17] .…”
Section: Introductionunclassified
“…TARTIŞMA TDY yaşamın her döneminde meydana gelebildiği gibi çocukların bu yaralanmalara daha sık maruz kaldığı bilinmektedir. 13,14 İlkokul çağındaki çocukların yaşları ve okullarda geçirdikleri uzun süreler nedeniyle travma sonucu meydana gelen diş yaralanmalarının büyük bir kısmı okullarda gerçekleşmektedir. 5 Kron kırıklarında kırık parçanın bulunması veya avülsiyona uğrayan dişlerin uygun ortamda taşınması gibi travmaya uğrayan bir dişe yapılacak doğru ve hızlı bir acil müdahale dişin prognozunu önemli ölçüde etkilemektedir.…”
Section: Vaka Iv: Dişin Tamamen Yerinden çıKmasıunclassified